Imports as product and labor market discipline - Hervé Boulhol; Sabien Dobbelaere; Sara Maioli (Institute for the Study of Labor (IZA), 2006)
This paper tests the pro-competitive effect of trade in the product and labor markets of UK manufacturing sectors between 1988 and 2003 using a two-stage estimation procedure. In the first stage, we use data on 9820 firms from twenty manufacturing sectors to simultaneously estimate mark-up and workers' bargaining power parameters according to sector, firm size and period. We find a significant drop in both the mark-up and the workers' bargaining power in the mid-nineties. In the second stage, we relate our parameters of interest to trade variables. Our results show that imports from developed countries have significantly contributed to the decrease in both mark-ups and workers' bargaining power.
Keywords: C23; F16; J51; L13; 330; workers' bargaining power; mark-ups; pro-competitive effect; Gewerkschaftlicher Organisationsgrad; Lohnverhandlungen; Internationaler Wettbewerb; Außenhandelseffekt; Schätzung; Verarbeitendes Gewerbe; Großbritannien